Synergistic Effect of Latex Powder and Rubber on the Properties of Oil Well Cement-Based Composites - Jianjian Song; Mingbiao Xu; Weihong Liu; Xiaoliang Wang; Yumeng Wu (Advances in Materials Science and Engineering)
The brittleness and the poor resistance to external load of oil well cement impede the development of oil and gas wells. To overcome these deficiencies, latex powder or rubber and their hybrid combinations were used to modify the oil well cement. The conventional properties, mechanical properties, and scanning electron microscopy (SEM) images of the modified cement were analyzed. In comparison with latex powder-incorporated cement and rubber-incorporated cement, a significant improvement of fluid loss, flexural strength, impact strength, and elasticity of the cement slurry was observed when using the hybrid combinations of 3 wt.% latex powder and 2 wt.% rubber, although this synergistic effect was not remarkable on the compressive strength and the thickening time. These evidences arose from the synergism between latex powder and rubber leading to the formation of a three-dimensional network structure and a flexible structure which subsequently improved the elasticity and toughness of cement stone. The improved elastic matrix has a buffering effect on external impact when the cement stone is subjected to an external load.